Paths to a Culture of Tolerance and Peace - EL Zein, Basma; Al Jarwan, Ahmed (Taylor & Francis, 2021)
We are living today in a multicultural world, surrounded by people from different backgrounds, cultures and religions. Establishing tolerance and peace has become crucial. Without these qualities, social stability and communal harmony are threatened; and acceptance of each other remains elusive. Spreading a culture of tolerance and peace is necessary to address contemporary issues of world peace, this includes reflection on the importance of refusing violence and adopting a more peaceful means for resolving disagreements and conflicts. This book, written by the world's foremost thinkers in this area, aims to increase feelings of openness and respect toward others, solidarity and sharing based on a sense of security in one's own identity and a capacity to recognize the many dimensions of being human in different cultural and social contexts. Topics discussed in the book include: Promoting Tolerance and Peace  Teaching Tolerance and Peace  Human Values  Intercultural / Interreligious dialogue  Human Fraternity document